Apakah infrastruktur sosial, indeks pembangunan manusia, dan pengangguran memengaruhi kemiskinan? perspektif maqashid syariah di Indonesia - Muhamad Andrian Setyo Nugroho; Saifudin Zuhri (Journal of Economics Research and Policy Studies, 2025)
Poverty remains a structural problem in Indonesia despite various development policies that have been implemented, particularly in the education, health, and employment sectors. The inconsistency of empirical findings and the dominance of conventional economic approaches underscore the need for a more comprehensive, value-based analytical framework. This study aims to analyze the influence of social infrastructure, the Human Development Index (HDI), and unemployment on poverty levels from the perspective of maqashid syariah. The method used in this study is panel data regression based on data from the Indonesian Central Statistics Agency (BPS). The results show that education has a positive and significant effect on poverty, indicating that ineffective, productivity-oriented educational development can increase poverty. Meanwhile, health has a positive but insignificant effect on poverty. Furthermore, HDI and unemployment have a negative and significant effect on poverty, indicating that integrated human development is effective in reducing poverty, and indicating that poverty is not solely determined by formal employment status. From the perspective of maqashid syariah, these findings confirm that poverty alleviation requires achieving overall maslahah by protecting reason, the soul, and property.